﻿RIGHTS FOR RECOGNITION OF "THE OTHER" IN JOE NUSSBAUM'S SYDNEY WHITE (2007): A SOCIOLOGICAL APPROACH - SETYAWAN. , ﻿WINDA RENNY (2011)
﻿The major problem of this study is how rights for recognition is reflected in Joe Nussbaum's Sydney White based on sociology of literature. The objectives of this study are to analyze Joe Nussbaum's Sydney White movie based on its structural elements and based on the sociology of literature. The benefits of this study are to given in the application of Sociological approach in literary study. The primary data is taken from the video and script of Sydney White movie, while the secondary data is taken from book and the information related to theory of sociology. The method of collecting data is library research. The technique of analyzing data is descriptive. The outcome of the study shows that based on the structural analysis its apparent that in this movie Joe Nussbaum's Sydney White conveys a moral message that the minority group tends to be the victims of oppression. Based on the sociological analysis, it is evident that in this movie, Nussbaum reflects the social realities of the America society, either social, political, economic, science and technology, religion, or cultural aspects